Evaluation of Antioxidant Activity On Plum Fruit (Prunus domestica L.) Skin Extract Applied For Natural Acid-Base Indicator - Said Ali Akbar (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2019)
Plum peel was extracted through the maceration method with 100 mL ethanol. This process obtained 5% (50 µg/µL) skin extract. The UV-Vis spectrum of the extract displayed the major absorption peak at λmax = 526 nm in acid media, this assigned by the electronic transition from flavylium which as characteristic of anthocyanin compounds. The of anthocyanins stability on temperature effect showed the absorbance decreases with the heating time, while the level of pigment color loss, or the percentage of color loss, gradually increases. The pigment was maintained at 100oC for 100 min with the loss rate reaches 58.5%. Therefore, The loss of anthocyanin color in the plum peel is relatively stable at lower temperatures. Then, The plum peels extract shown the red color at pH 1-3, almost colorless at pH 4-7, and violet color at pH 12. Finally, plum peels extract was potentially used as the acid-base indicator.